2009
DOI: 10.1038/sj.bjc.6605014
|View full text |Cite
|
Sign up to set email alerts
|

International consensus for neuroblastoma molecular diagnostics: report from the International Neuroblastoma Risk Group (INRG) Biology Committee

Abstract: Neuroblastoma serves as a paradigm for utilising tumour genomic data for determining patient prognosis and treatment allocation. However, before the establishment of the International Neuroblastoma Risk Group (INRG) Task Force in 2004, international consensus on markers, methodology, and data interpretation did not exist, compromising the reliability of decisive genetic markers and inhibiting translational research efforts. The objectives of the INRG Biology Committee were to identify highly prognostic genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
285
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(303 citation statements)
references
References 54 publications
(73 reference statements)
8
285
1
5
Order By: Relevance
“…This concept has been established for HER2 testing in breast cancer and MYCN testing in neuroblastoma, although the cutoffs used in our current study vary somewhat from those that define 'copy number gain' or 'amplification' in HER2 and NMYC testing. 25,26 We identified 54 RCCs with ALK copy number gain (Z5 copies). We also identified an association between the presence of Z5 copies of ALK and a poorer cancer-specific survival in patients with CCRCC but not in PRCC.…”
Section: Discussionmentioning
confidence: 99%
“…This concept has been established for HER2 testing in breast cancer and MYCN testing in neuroblastoma, although the cutoffs used in our current study vary somewhat from those that define 'copy number gain' or 'amplification' in HER2 and NMYC testing. 25,26 We identified 54 RCCs with ALK copy number gain (Z5 copies). We also identified an association between the presence of Z5 copies of ALK and a poorer cancer-specific survival in patients with CCRCC but not in PRCC.…”
Section: Discussionmentioning
confidence: 99%
“…These tumours uniformly exhibit an immature cellular phenotype, reflecting their origin from early embryonic populations such as sympathoadrenal progenitors for neuroblastoma and metanephric progenitors for nephroblastoma. While many SRBCT subtypes exhibit characteristic chromosomal rearrangements [12][13][14][15][16] , next-generation sequencing studies have shown relatively few DNA sequence mutations in childhood cancers compared with adult neoplasms 8 . The present study of intratumoral heterogeneity in SRBCTs therefore focused on genomic aberrations larger than point mutations, that is, those detectable by high-resolution genotyping arrays.…”
Section: Intratumoral Genome Diversity In Treated Childhood Cancersmentioning
confidence: 99%
“…Comparing the number of MYCN signals and centromere 2 signals, all cases were scored as MYCN-gained and none as MYCN amplified. 33 The proportion of neuroblasts with MYCN gain varied from case to case, ranging from 10% (case 6) up to 61% (case 3) with the remainder in the 22-48% range. Four of the cases with MYCN gain also showed gain in ganglion cells (cases 2, 4, 5, and 8) with up to 17 copies in 1 ganglion cell in case 4 and 10-15 copies in 40% ganglion cells in case 8 (Figure 1b), whereas the neuroblastoma component showed up to 5 copies of MYCN per neuroblast.…”
Section: Mycn Copy Number Gain In Neuroblasts and Ganglion Cells Frommentioning
confidence: 99%